Penguatan Literasi Sastra di Sekolah Melalui Pelatihan Apresiasi Cerita Rakyat Lokal Untuk Menumbuhkan Karakter Siswa di SMPN 2 Selong - Eva Nurmayani; Muh. Jaelani Al Pansori; Lia Rismawati (BALE LITERASI, 2025)
This Community Service Program (PkM) aims to strengthen students’ literary literacy through training in the appreciation of local folklore to foster students’ character development at SMPN 2 Selong. This program was motivated by several issues, including students’ low level of literary literacy, literature instruction that remains focused on memorization, and the limited integration of character education in Indonesian language learning. The program employed a participatory approach consisting of planning, implementation of literary appreciation training, mentoring, and evaluation stages. The training materials emphasized understanding the intrinsic elements of folklore, interpreting moral values, and reflecting on character values relevant to students’ daily lives. The results indicate a significant improvement in students’ literary literacy, particularly in their ability to comprehend story content, identify literary elements, interpret moral messages, and express ideas both orally and in written form. In addition, the program contributed to the strengthening of character values such as honesty, responsibility, cooperation, and social awareness. Folklore-based literary learning also enhanced students’ motivation, participation, and active engagement in the learning process. These findings demonstrate that the appreciation of local folklore can serve as an effective and contextual alternative strategy for literary learning. Therefore, this program has the potential to be implemented sustainably to support the development of literary literacy and character education in secondary schools.